2017
DOI: 10.1111/bju.13991
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and safety of focal irreversible electroporation as salvage treatment for localized radio‐recurrent prostate cancer

Abstract: Objectives To evaluate the feasibility, safety, early quality‐of‐life (QoL) and oncological outcomes of salvage focal irreversible electroporation (IRE) for radio‐recurrent prostate cancer (PCa). Patients and Methods Patients with localized, radio‐recurrent PCa without evidence of metastatic or nodal disease were offered focal IRE according to the consensus guidelines. Patients with a minimum follow‐up of 6 months were eligible for analysis. Adverse events were monitored using the National Cancer Institute Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 33 publications
3
39
0
Order By: Relevance
“…Another recent prospective cohort study of 30 patients, with a median follow-up of 20 months, reported similar oncological and function outcomes [32]. The results of studies applying IRE are shown in Table 2 [22][23][24][25][26][27][30][31][32]37,48].…”
Section: Clinical Trials Of Ire In Prostate Cancermentioning
confidence: 86%
“…Another recent prospective cohort study of 30 patients, with a median follow-up of 20 months, reported similar oncological and function outcomes [32]. The results of studies applying IRE are shown in Table 2 [22][23][24][25][26][27][30][31][32]37,48].…”
Section: Clinical Trials Of Ire In Prostate Cancermentioning
confidence: 86%
“…Increased use of EBRT has been observed in the USA, from 11.6% to 24% in the same period . Reasons for these trends may include changes in PSA testing, use of MRI and prostate biopsy, AS, robotic surgery and newer focal therapies (such as Cyberknife or irreversible electroporation ) that may be better clarified after further analysis with the maturation of the Prostate Cancer Outcomes Registry of Australia and New Zealand .…”
Section: Discussionmentioning
confidence: 99%
“…Following pretreatment imaging [currently performed with mpMRI or transperineal template mapping prostate biopsy (TTMP)], IRE is conducted with transperineal placement of probes under ultrasound guidance to establish an ablative field (86)(87)(88)(89). Presently, the NanoKnife platform (Angiodynamics, Queensbury, NY), is the only FDA 501(k) cleared IRE system, although it has limited clinical use thus far.…”
Section: Irementioning
confidence: 99%
“…In a number of clinical studies (Table 4) followup consisted of an mpMRI with contrast 1-6 weeks after IRE, mpMRI at 6 months, and repeat biopsy at 6 months to 1 year. PSA was assayed at 3-month intervals (87)(88)(89). Occasionally, contrast-enhanced ultrasound (CEUS) was used for pre-treatment and post-treatment imaging (91,92).…”
Section: Irementioning
confidence: 99%
See 1 more Smart Citation